ANALISIS SISTEM PENGENDALIAN INTERNAL PADA SISTEM AKUNTANSI PEMERINTAH (STUDI KASUS PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN SEMARANG) - Irma Damayanti (KRISNA: Kumpulan Riset Akuntansi, 2020)
The aim of this study is to analyze the appropriateness of the application of the internal control system carried out at government agencies based on the elements of internal control. The analysis uses descriptive research method and the type of research used is qualitative research. The object of this research is the Ministry of Communication and Information of Semarang Regency. The result shows that the application of the internal control system in the Ministry of Communication and Information of Semarang Regency is in accordance with the elements of the Internal Control System set by the government based on the Government Regulation No. 60 year 2008, but there are some deficiencies such as the number of students internships received exceeds the limit, some employees who perform the main duties of supervision, budgeting, and planning do not have economic education background especially accounting, and warehouse facility provided for documents and belongings are not efficient.